2018
DOI: 10.1002/cam4.1292
|View full text |Cite
|
Sign up to set email alerts
|

CTAPIII/CXCL7: a novel biomarker for early diagnosis of lung cancer

Abstract: It is desirable to have a biomarker which can facilitate low‐dose CT in diagnosis of early stage lung cancer. CTAPIII/CXCL7 is reported to be a potential biomarker for diagnosis of early lung cancer. In this study, we investigated the serum level of CTAPIII/CXCL7 in patients at different stage of lung cancer and the diagnostic efficacy of CTAPIII/CXCL7 in NSCLC. The plasma level of CTAPIII/CXCL7 was assayed by ELISA. CEA, SCCAg, and Cyfra211 were measured using a commercial chemiluminescent microparticle immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
(47 reference statements)
0
20
1
Order By: Relevance
“…1,2 Many patients with NSCLC were diagnosed at the advanced stage. 3 At present, the treatment methods are limited for patients with advanced and metastatic NSCLC. Obviously, it is urgent to discover indicators for early diagnosis and new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many patients with NSCLC were diagnosed at the advanced stage. 3 At present, the treatment methods are limited for patients with advanced and metastatic NSCLC. Obviously, it is urgent to discover indicators for early diagnosis and new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal cancer, the Iroquois Homeobox 6 (IRX6) expression has been reported to be lower in tumor samples and was a prognostic predictor [30]. Pro-platelet basic protein (PPBP) was also known as C-X-C motif chemokine ligand 7 (CXCL7), the overexpression of which has been reported to promote cell proliferation in vivo and in vitro, and it has been proposed as a novel biomarker for the diagnosis of lung cancer and renal cell carcinoma [31][32][33]. Zhou et al reported that Empty spiracles homeobox 1 (EMX1) was a potential target of miR-497, which was recognized as a tumor suppressor in many cancers, and the high expression of EMX1 was related to advanced clinicopathologic characteristics in endometrial cancer [34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the overexpression of most of these genes in multiple cancers, with the exception of CH507-9B2.3 [50,51,52,53,54]; however, they have also been found to be down-regulated in some specific cancers. For example, the chemokine PPBP (pro-platelet basic protein), also known as CXCL7, is decreased in pancreatic and ovarian cancers [55]. The eukaryotic translation elongation factors EEF1B2 and EEF2 are down-regulated in breast, esophageal, and lung cancers while EEF1B2 is found with repression in some other cancer types, such as head and neck, leukemia, and pancreatic cancer [54].…”
Section: Discussionmentioning
confidence: 99%